Mendorong Sikap Toleransi Melalui Pembelajaran Pendidikan Pancasila - Ferdyan Hanif Katsirun Nawwal; Hanung Hanindhito; Nur Indah Wahyuni (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses strategies for encouraging attitudes of tolerance through learning Pancasila Education. Pancasila education is considered an effective means of forming students' characters who respect differences and have a tolerant attitude towards diversity in society. This article explores the role of teachers in creating a learning environment that supports the development of attitudes of tolerance, taking into account the principles of Pancasila. The research design was through classroom action research (PTK) which was carried out in 2 meetings. The subjects of observation were 25 class V students at SD Negeri Podorejo 02, totaling 25 people for the 2023/2024 academic year. From the learning practices that have been carried out by researchers, it shows that there is an increase in students' interest in learning, which influences the achievement of students' learning outcomes so that from this increase they can find an attitude of tolerance in students' daily activities. It was concluded that after carrying out these two cycles, students were able to develop an attitude of tolerance through learning Pancasila education.